Death in an elegant city eaudiobook - Rosett, Sara (Murder on Location, 2019)
Sightseeing can be murder . . . Location scout Kate Sharp is thrilled to be part of a scouting trip to the historic city of Bath, England to research the location for a Jane Austen documentary. But before Kate gets a chance to stroll the elegant boulevards where Austen once lived, murder cuts the sightseeing short. Now Kate must rearrange her itinerary and find the killer before she and the production are shut down permanently. Perfect for fans of British detective mysteries, Death in an Elegant City blends the puzzle of a whodunit with the mystique of Jane Austen. It is the fourth installment in the popular Murder on Location series, a collection of traditional British cozy mysteries. Escape into a quintessentially English cozy with a Sara Rosett mystery today!